A LEGISLATIVE FRAMEWORK CHANGE ON PUBLIC SERVICES FOR THE CARRIAGE OF PASSENGERS (Perner's Contacts, 2009)
The paper deals with upcoming changes to the legislative framework of public services for the carriage of passengers from the perspective of European Union laws and methods of law standards in the Czech Republic.
Keywords: European Union; regulation; law; public transport; carriage of passengers